Towards a Conceptualization of Social Entrepreneurship in Higher Education - Carmen Păunescu; Denisa Drăgan; Ramona Cantaragiu; Adina Filculescu (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
The paper aims to investigate multiple meanings and conceptualizations of social entrepreneurship in nonprofit, business and higher education sector. In the paper, the characteristics of university social entrepreneurship are investigated and the driving forces that determine the social entrepreneurial behavior of academic community members are discussed. Also, possible links between social responsibility and social entrepreneurship in higher education are addressed. The conceptual model that is proposed is based on a thorough review of the recent literature on academic entrepreneurship, social responsibility, and social entrepreneurship. Also, secondary data in the form of official reports and other relevant documents available on universities' and public and non-governmental organizations' websites have been scrutinized. The examination reveals that, generally, universities experiment with different models of entrepreneurship, both business and social. Our findings also suggest that universities which are society-oriented and driven by a social mission are more likely to transform into social entrepreneurial institutions than the others. The paper argues that a university with an entrepreneurial culture embedded in all organizational processes and institutionalized at all managerial levels tends to be more concerned with addressing current society problems or unsolved market needs. Our findings need to be further tested empirically in future researches.
Keywords: 650; university engagement; social entrepreneurial behavior; social entrepreneurship; university entrepreneurship; social responsibility